A third endemic Artena from the Philippines (Lepidoptera: Erebidae) - Zilli, Alberto; de Vos, Rob (Fragmenta entomologica, 2020)
Artena uncinata sp. n. from the Philippines (Luzon) is described. This species is a third member of the A. lacteicincta-A. eccentrica group and can readily be separated from its closest allies by the reduced secondary sexual characters of the male and differences in the male genitalia.